Effect of carbon addition and VC on mechanical properties in ultra-fine WC-Co cutting tool / Nurul Nazihah Ismail - Ismail, Nurul Nazihah (2017)
Cemented tungsten carbide (WC-Co) is one of the most favourable material used in fabrication of cutting tools. High challenge in machining especially in machining hard material have accelerates the development of these engineered materials with enhanced properties. With addition of specific additives such as carbon (C) and vanadium carbide (VC) contributes to different improvement on the mechanical properties of the cutting tools. The addition of C in WC-Co composite will improve the hardness properties while the addition of VC will inhibit the grain growth. In this work, the effects of different composition of C and VC addition in ultra-fine WC-Co cutting tools on the mechanical properties such as the density, hardness and transverse rupture strength (TRS) are investigated. WC-Co powders mixed with 0.2%VC and 0.2%C. The mixed powders are compacted and sintered as per conventional powder metallurgy (PM) route. Mechanical properties of sintered cutting tools are measured such as the hardness of the cutting tool using Vickers Hardness Test and transverse rupture strength (TRS) using the Universal Testing Machine. The microstructure of the sintered samples are observed using Scanning Electron Microscope. The results show that the highest hardness and TRS are 2041MPa and 2725HV respectively which is obtained at the composition of WC-Co- 0.2%C-0.2%VC.